2014
DOI: 10.1161/jaha.113.000527
|View full text |Cite
|
Sign up to set email alerts
|

Calpain‐Dependent Cleavage of Junctophilin‐2 and T‐Tubule Remodeling in a Mouse Model of Reversible Heart Failure

Abstract: BackgroundA highly organized transverse tubule (T‐tubule) network is necessary for efficient Ca2+‐induced Ca2+ release and synchronized contraction of ventricular myocytes. Increasing evidence suggests that T‐tubule remodeling due to junctophilin‐2 (JP‐2) downregulation plays a critical role in the progression of heart failure. However, the mechanisms underlying JP‐2 dysregulation remain incompletely understood.Methods and ResultsA mouse model of reversible heart failure that is driven by conditional activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 67 publications
(167 reference statements)
3
68
0
Order By: Relevance
“…In cardiac muscle cells, the loss of JPH2 has previously been shown to play a major role in the organisation of the t-tubules Wei et al, 2010;Wu et al, 2014;Chen et al, 2013). In addition to control and JPH2-OE myocytes, JPH2-KD myocytes were also included as a sample with known changes in t-system properties .…”
Section: T-tubule System Changes In Cells With Altered Jph2mentioning
confidence: 99%
“…In cardiac muscle cells, the loss of JPH2 has previously been shown to play a major role in the organisation of the t-tubules Wei et al, 2010;Wu et al, 2014;Chen et al, 2013). In addition to control and JPH2-OE myocytes, JPH2-KD myocytes were also included as a sample with known changes in t-system properties .…”
Section: T-tubule System Changes In Cells With Altered Jph2mentioning
confidence: 99%
“…Moreover, mutations in the JP2 coding region have been discovered in patients with hypertrophic cardiomyopathy (13,14). The pathological relevance of JP2 has been revealed by observations that dysregulation of JP2 protein is associated with pathological progression in multiple models of heart failure, including pressure overload-induced hypertrophy/heart failure and myocardial infarction (15)(16)(17)(18)(19)(20)(21). Toward understanding the mechanism of JP2 down-regulation, a recent report has demonstrated that JP2 is targeted by the microRNA miR-24, which may be responsible for the down-regulation of JP2 during long-term pressure overload-induced hypertrophy and heart failure (19,22).…”
mentioning
confidence: 99%
“…Recently, a Ca 2ϩ -dependent mechanism of junctophilin proteolysis has been reported (23). More specifically, the activity of calpain, a family of Ca 2ϩ -dependent proteases has been found to be related to the degradation of JP2 (21). However, it remains unclear whether JP2 is a direct substrate of calpain and the specific molecular site for JP2 proteolysis.…”
mentioning
confidence: 99%
“…At the molecular scale, several candidate proteins have been identified that are required for normal junctional structure and appear to be involved in t-tubule remodelling in heart failure (van Oort et al 2011;Zhang et al 2014;Hong et al 2014;Wu et al 2014;Guo et al 2014;Caldwell et al 2014). The first of these proteins identified was junctophilin-2 (JPH2), a protein that forms a connection between the plasma and SR membranes.…”
Section: Mechanisms Of T-tubule Remodellingmentioning
confidence: 99%
“…Microtubule densification, a known feature of heart failure, was later linked to defective JPH2 trafficking and t-tubule remodelling . Loss of JPH2 and t-tubule remodelling has also been linked to overactivation of heterotrimeric G protein Gαq that occurs in cardiac hypertrophy (Wu et al 2014;Huang et al 2016). Recently, a novel junctional protein, striated muscle preferentially expressed protein kinase (SPEG), has been identified and its knockout in mice, leading to t-tubule remodelling, aberrant local Ca 2+ handling and heart failure (Quick et al 2016).…”
Section: Mechanisms Of T-tubule Remodellingmentioning
confidence: 99%